Hiding from Whom? Threat Models and In-The-Making Encryption Technologies - Ermoshina, Ksenia; Musiani, Francesca (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2018)
Following Edward Snowden’s revelations, end-to-end encryption is becoming increasingly widespread in messaging tools—solutions that propose a large variety of ways to conceal, obfuscate, disguise private communications and online activities. Designing privacy-enhancing tools requires the identification of a threat model that serves to agree upon an appropriate threshold of anonymity and confidentiality for a particular context of usage. In this article, we discuss different use-cases, from “nothing-to-hide” low-risk situations to high-risk scenarios in war zones or in authoritarian contexts, to question how users, trainers, and developers co-construct threat models, decide which data to conceal, and how to conceal it. We demonstrate that classic oppositions such as high-risk versus low-risk, privacy versus security, should be redefined within a more relational, processual, and contextual approach.